Knowledge and attitude of pain management among Italian nurses in intensive care unit: a multicentric descriptive study - Damico, V.; Murano, L.; Macchi, G.; Forastieri Molinari, A.; Dal Molin, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim. The main objective of the study was to document the current knowledge and attitudes towards pain management among Italian nurses working in intensive care unit (ICU).Methods. A multicenter cross-sectional study design was carried out. In order to assess the knowledge and attitudes of pain management, the KASRP questionnaire was used. The questionnaire was submitted online through Google Forms platform. Results. A total of 864 nurses completed and returned the study questionnaire (58% were males). The mean of the total correct answers was 31.21 (SD 2.92) out of 40 (total score if all items answered correctly) with range of 22–38. No significant differences were observed with regard to gender (t = 1.875, P = .061). Spearman’s correlation test showed a positive significant relationship between knowledge and attitude of pain management and years of ICU experience (r = -.424, P